PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION (RME) SECARA DARING PADA MATERI BARISAN DAN DERET - Titin Ifati (Direktorat Guru Pendidikan Menengah dan Pendidikan Khusus, 2022)
The purpose of this study is to describe online Realistic Mathematics Education learning on the material of sequences and series. This research is a descriptive research with a qualitative approach. The researchwas given to 36 students of class XI IPA 6 SMA Negeri 1 Driyorejo, consisting of 15 males and 21 females.The research was carried out by applying Realistic Mathematics Education (RME) online learning, using google classroom, WhatsApp group and Google meet. The results of learning observations indicate that the teacher has carried out learning in accordance with the online Realistic Mathematics Education (RME) learning design. The results of the student response questionnaire at the end of the learning activity after calculating the average percentage of students who gave a positive response was 77.8%. Based on the criteria that have been set, it can be said that the response of students to learning is good. Student learning outcomes increased after Realistic Mathematics Education (RME) learning was carried out. This is because in Realistic Mathematics Education (RME) learning, students use the real world to construct knowledge so that it is easier for them to understand the material.